1998
DOI: 10.1016/s0921-4534(98)00283-4
|View full text |Cite
|
Sign up to set email alerts
|

Variational Monte Carlo study on the superconductivity in the two-dimensional Hubbard model

Abstract: Ž .Ž . The possibility of superconductivity SC in the ground state of the two-dimensional 2D Hubbard model was investigated by means of the variational Monte Carlo method. The energy gain of the d-wave SC state, obtained as the difference of the minimum energy with a finite gap and that with zero gap, was examined with respect to dependences on U, electron density r and next nearest neighbor transfer t X mainly on the 10 = 10 lattice. It was found to be maximized around Ž .X U s 8 the energy unit is nearest ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
82
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 41 publications
8
82
0
Order By: Relevance
“…Condensation energy E cond for the SC state is obtained as the decrease per site of this E g from the normal state energy similarly calculated starting from the normal state trial wave function [6]. E cond for the commensurate SDW state is obtained similarly.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Condensation energy E cond for the SC state is obtained as the decrease per site of this E g from the normal state energy similarly calculated starting from the normal state trial wave function [6]. E cond for the commensurate SDW state is obtained similarly.…”
Section: Model and Methodsmentioning
confidence: 99%
“…The idea behind this originally proposed by Anderson 4 is that mobile hole pairs are created via a strong on-site repulsion U. Results by Paramekanti et al 5 and Yamaji et al, 6 using a variational Monte Carlo ͑VMC͒ simulation with a ͑projected͒ BCS-type trial-wave function, appeared to back this up. More recently Yamaji et al 7 found a condensation energy in a Hubbard model with next-and third-neighbor hopping but not in the simplest nearest-neighbor Hubbard model.…”
mentioning
confidence: 99%
“…6 Our variational parameters are g and the chemical potential that enters through the kinetic energy k ϵ −2t͑cos k x + cos k y ͒ − via u k…”
mentioning
confidence: 99%
See 2 more Smart Citations